Implementasi Sistem Otomatisasi Berbasis ERP Pada Perusahaan Logistik - Ashari, Yogi; Indriyati, Indriyati; Setyowati, Tri Mulyani (Institut Transportasi dan Logistik Trisakti, 2024)
This scientific journal explores the impact of Enterprise Resource Planning (ERP) system implementation on the logistics management of supply chain enterprises. The research aims to assess the significance of Human Resource Competency and Employee Training in relation to ERP-based automation implementation. Additionally, it investigates the influence of ERP implementation on logistics activities' efficiency, effectiveness, increased company profit, enhanced employee productivity, and potential employee restructuring. The study utilizes Structural Equation Modelling (SEM) based on Partial Least Square (PLS) to analyze the data. The ERP system has become crucial in modern businesses due to the rapid development of information technology and the need for improved logistics efficiency. Establishing a logistics management information system using ERP provides a competitive advantage for companies in managing their logistics operations effectively. The study analyzes complex logistics business processes and designs an ERP-based logistics information management system to enhance customer satisfaction significantly.